- Strategi Pengembangan Sapi Perah LEISA Berkelanjutan di Kabupaten Kolaka Timur - Nur Santy Asminaya; Fuji Astuti Auza; Dian Agustina; Musram Abadi; Andi Murlina Tasse; Fahri Akbar (Postgraduate, University of Mataram, 2026)
This study aims to formulate a strategy for sustainable dairy cattle development using the LEISA (Low External Input Sustainable Agriculture) production approach in East Kolaka Regency, Southeast Sulawesi. The study was conducted in Lalolae and Ladongi Districts, which were purposively selected as dairy cattle development areas. Primary data were collected through interviews, observation, and documentation, while secondary data were obtained from relevant institutions. Data analysis used the IFE, EFE, IE, SWOT, and QSPM matrices. The results showed that the IFE (3.54) and EFE (3.70) values were in a strong internal position and a supportive external environment, placing the dairy cattle business in Quadrant I of the IE matrix. This position reflects a